Early start of the West Nile fever transmission season 2018 in Europe - Haussig, Joana M.; Young, Johanna J.; Gossner, Céline M.; Mezei, Eszter; Bella, Antonino; Sirbu, Anca; Pervanidou, Danai; Drakulovic, Mitra B.; Sudre, Bertrand (Euro surveillance : bulletin européen sur les maladies transmissibles, 2018)
In Europe, surveillance indicates that the 2018 West Nile fever transmission season started earlier than in previous years and with a steeper increase of locally-acquired human infections. Between 2014 and 2017, European Union/European Economic Area (EU/EEA) and EU enlargement countries notified five to 25 cases in weeks 25 to 31 compared with 168 cases in 2018. Clinicians and public health authorities should be alerted to ensure timely implementation of prevention measures including blood safety measures.